The influence of transformational leadership and religiosity on performance of village apparatus in Sungai Penuh City with organizational citizenship behavior as an intervening variable - Deky Hamdani; Fadli Anugrah; Ayu Esteka Sari (Trigin Publisher, 2023)
The purpose of this study is to analyze how the The influence of transformational leadership and religiosity on performance of village apparatus in Sungai Penuh City with organizational citizenship behavior as an intervening variable. The research was conducted in Sungai Penuh City in Jambi Province. This study used quantitative research methods. To obtain valid data and information, researchers use interviews, observation, surveys, and documentation techniques. Model Testing Techniques using Structural Equation Model (SEM) with AMOS. The population is the entire village apparatus in Sungai Penuh City. The sampling technique is an accidental sampling method, with the number of samples representing the population with a total of 115 responses. The result of the research that R-square value of exogenous latent variables to endogenous latent variables is: The magnitude of the influence of Religiosity, Transformational leadership and organizational citizenship behavior on performance was 0.522 or 52.2%. That is, religiosity, transformational leadership and organizational citizenship behavior have an influence of 52.2%. While the magnitude of the influence of organizational citizenship behavior is 0.357 or 35.7%. That is, religiosity and transformational leadership have an influence of 35.7. Meanwhile, the remaining 64.3% was explained by other variables outside the research model.